2021
DOI: 10.15212/zoonoses-2021-1001
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in Chest CT Images Over 167 Days in 11 Patients with COVID-19: A Case Series and Literature Review

Abstract: Background: Recently, CT findings have been widely reported to be associated with the clinical severity of COVID-19. However, few studies have reported the correlation between CT findings and long-term outcomes in patients with COVID-19. Case presentation: Herein, we conducted a 167 day long-term follow-up of CT examination on 11 patients with COVID-19 to evaluate their long-term prognosis, particularly in severe cases. We found that the course of COVID-19 can be divided into four stages according to the cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Clinical, chest CT, and postmortem findings have shown that fibrosis and restriction of pulmonary function are frequently present in patients who have recovered from COVID-19: (i) more than a third of the patients with severe forms of COVID-19 may show limited lung function after hospital discharge [12,13], (ii) PF on chest CT have been reported in patients who had recovered from severe or critical disease [12][13][14], and (iii) in an autopsy study involving patients with acute respiratory distress syndrome (ARDS), the finding of PF was more frequent as more time had elapsed since the onset of clinical manifestations of COVID-19 [15]. PF is already recognized among the most important sequelae of SARS-CoV-2 infection [16].…”
Section: Pulmonary Fibrosis (Pf) Of Postacute Covid-19 Syndrome (Pacs)mentioning
confidence: 99%
“…Clinical, chest CT, and postmortem findings have shown that fibrosis and restriction of pulmonary function are frequently present in patients who have recovered from COVID-19: (i) more than a third of the patients with severe forms of COVID-19 may show limited lung function after hospital discharge [12,13], (ii) PF on chest CT have been reported in patients who had recovered from severe or critical disease [12][13][14], and (iii) in an autopsy study involving patients with acute respiratory distress syndrome (ARDS), the finding of PF was more frequent as more time had elapsed since the onset of clinical manifestations of COVID-19 [15]. PF is already recognized among the most important sequelae of SARS-CoV-2 infection [16].…”
Section: Pulmonary Fibrosis (Pf) Of Postacute Covid-19 Syndrome (Pacs)mentioning
confidence: 99%
“…Currently, although WHO has approved more than ten vaccines for emergency use (https://www.who.int/teams/regulation-prequalification/eul/COVID-19), and dozens of vaccines are approved by different countries, the spread of the COVID-19 pandemic is still not effectively contained [3] , [4] , [5] , [6] . More notably, SARS-CoV-2 variants keep emerging and may break through the protection of existing vaccines [7] , [8] , [9] .…”
Section: Introductionmentioning
confidence: 99%